2015
DOI: 10.2298/abs150407107k
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant responses of peanut (Arachis hypogaea L.) seedlings to prolonged salt-induced stress

Abstract: In this study, the effects of long-term NaCl treatment were investigated in two cultivars of peanut designated as drought-resistant and drought-sensitive. Growth parameters, changes in the concentrations of MDA, H2O2 and proline, and the activities of antioxidant enzymes were determined under salinity stress. Growth parameters indicated the superiority of cv. Florispan to cv. Gazipa?a under milder salinity stress treatment. However, comparative analysis of the two cultivars showed that MDA, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…The most common and significant effect of salt and drought stresses on plants is the inhibition of growth and biomass production (Kavas et al 2015). Our results showed that SD1 and SD2 decreased G. uralensis growth and biomass compared with control, and this adverse effect was partly reversed by Si addition (Table 2 and 3), which is consistent with previous findings in sugarcane (Ashraf et al 2010), G. uralensis seedlings (Zhang et al 2017), and canola (Hashemi et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…The most common and significant effect of salt and drought stresses on plants is the inhibition of growth and biomass production (Kavas et al 2015). Our results showed that SD1 and SD2 decreased G. uralensis growth and biomass compared with control, and this adverse effect was partly reversed by Si addition (Table 2 and 3), which is consistent with previous findings in sugarcane (Ashraf et al 2010), G. uralensis seedlings (Zhang et al 2017), and canola (Hashemi et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…However, to date little is known about the effect of abiotic stress on phytochemical accumulation in edible sprouts and the application of environmental stress to enhance their quality traits as well as the actual translatability of the enriched-bioactive compounds to biological benefits in lifestyle-related diseases. The effect of salt stress on bioactive compounds accumulation was studied in sprouts of radish (Yuan et al, 2010), broccoli (Guo et al, 2014), lentil (Świeca, 2015), peanut (Kavas et al, 2015), alfalfa ) and buckwheat (Lim et al, 2012). In wheat (Triticum aestivum L.) the impact of salt stress was only evaluated in terms of germination rates and biometric determinations (Datta et al, 2009) while no quality trait was assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Carrasco-Rios and Pinto (2014) 33 grew the maize plants in 50 and 100mM NaCl stress and reported decreased catalase activity in plant shoots at 100mM NaCl stress. Kavas et al (2015) 13 treated two 12-day old peanut cultivars with 0/100/ 300mM NaCl for 16 days and found decreased catalase activity in both. Naik et al (2016) 16 treated 10-day old niger plants with 0-500mM NaCl for 24/48/72 hours and reported reduction in catalase activity.…”
Section: Assays Of Enzymesmentioning
confidence: 99%
“…However, majority of reports are of increase. Salt stimulated GR increase has also been reported in a number of plants like Gossypium hirsutam (0-150mM NaCl for 30 days) 34 , Phaseolus vulgaris (5-day old plants with 400mM NaCl for 48 hours) 35 , Atriplex hortensis (260mM NaCl for 3 months) 32 , Zea mays (21 day old two maize varieties in 0/50mM/100mM NaCl for 15 days) 35 , Arachis hypogea (two 12-day old peanut cultivars with 0/100/ 300mM NaCl for 16 days) 13 , chickpea (0-200 mg L −1 NaCl) 15 , Brassica juncea (250mM NaCl stress for 6 hours) 17 and Guizotia abyssinica (0-500mM NaCl for 24/48/72 hours) 16 .…”
Section: Assays Of Enzymesmentioning
confidence: 99%
See 1 more Smart Citation